FATIGUE LIFE ANALYSIS OF PLANET CARRIER OF SHEARER CUTTING UNIT BASED ON LOAD RECONSTRUCTION THEORY - CHEN HongYue; ZHANG Kun; WANG Xin; MAO Jun; SONG QiuShuang; YUAN Zhi; XU JianBo (Jixie qiangdu)
In order to study the fatigue life of the planet carrier in the actual working conditions,through the cutting experiment,the three-force loads was obtained,and the reconstruction function of the three-force load was established. The method of the SOR method was used to solve the reconstruction function. According to the roller structure parameters,the load torque of the planet carrier was performed. Using ANSYS Workbench transient dynamic analysis on the dynamics of the planet carrier,and the torque was loaded in the form of the time series to planet carrier,the results file to import ncode of planet carrier life prediction and simulation results show that: The service life of the output shaft and the side wall panel is small,which shows that the geometrical size of the output shaft is larger,and the stress concentration phenomenon exists.